2014
DOI: 10.1007/s12012-014-9282-y
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-Based Herbicides Potently Affect Cardiovascular System in Mammals: Review of the Literature

Abstract: In glyphosate (G)-based herbicides (GBHs), the declared active principle G is mixed with several adjuvants that help it to penetrate the plants' cell membranes and its stabilization and liposolubility. Its utilization is growing with genetically modified organisms engineered to tolerate GBH. Millions of farmers suffer poisoning and death in developing countries, and occupational exposures and suicide make GBH toxicity a worldwide concern. As GBH is found in human plasma, widespread hospital facilities for meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 55 publications
1
40
0
6
Order By: Relevance
“…Although glyphosate has low oral acute mammalian toxicity, a considerable number of animal and epidemiological studies have demonstrated the toxicity of commercial glyphosate products (Cattani et al, ; Gress et al, ; Milesi et al, ; Tang et al, ; Wunnapuk et al, ). The kidney may be the main target of glyphosate‐based herbicides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although glyphosate has low oral acute mammalian toxicity, a considerable number of animal and epidemiological studies have demonstrated the toxicity of commercial glyphosate products (Cattani et al, ; Gress et al, ; Milesi et al, ; Tang et al, ; Wunnapuk et al, ). The kidney may be the main target of glyphosate‐based herbicides.…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate‐based herbicides may have neurotoxicity, cardiovascular toxicity, hepatotoxicity, reproductive and developmental toxicity, and nephrotoxicity (Cattani et al, ; Gress, Lemoine, Seralini, & Puddu, ; Milesi et al, ; Tang, Hu, Li, Win‐Shwe, & Li, ; Wunnapuk et al, ); however, the underlying mechanisms are not fully understood. There are some epidemiological studies suggesting a potential relationship between glyphosate‐based herbicides (together with other factors) and chronic kidney disease of unknown etiology (CKDu) (Jayasumana, Gunatilake, & Senanayake, ; Jayasumana et al, ; Peraza et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, glyphosate has been potentially correlated with disruption of glycine homeostasis (Pérez-Torres et al, 2017) and pathological conditions e.g., autism (Nevison, 2014), fatal chronic kidney disease (in regions with heavy metal contamination in water) (Jayasumana et al, 2014(Jayasumana et al, , 2015, bronchial inflammation (Kumar et al, 2014), cardiovascular diseases (Gress et al, 2015), and cancer (Paumgartten, 2017). Dermatology problems upon skin contact with glyphosate-based herbicides have also been reported (Amerio et al, 2004;Heras-Mendaza et al, 2008;de Ávila et al, 2017;Elsner et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“…42 Maruziyet artışı ve yüksek plazma glifosat konsantrasyonları (>734 mg/mL) ile ölüm görülme sık-lığı arasında ilişki olduğu bulunmuştur. 43 …”
Section: Kardi̇yovasküler Si̇stem Etki̇leri̇unclassified